We use cookies to personalise content and advertisements and to analyse access to our website. Furthermore, our partners for online advertising receive pseudonymised information about your use of our website.
Please click on "Accept cookies" if you agree to the setting of cookies. Cookies that do not require consent remain unaffected by this, see
cookie policy and privacy policy.
DECLINE COOKIES

#1**+2 **

Here's a geometric proof of the Pythagorean Theorem using similar triangles :

Let ABC be a righ triangle with a right angle at C

And CD is an altitude with right angles ADC and BDC

We want to prove that AC^2 + BC^2 = AB^2

So...looking at triangles ABC and ADC

Angle A = angle A

Angle ACB = angle CDA

So...by AA congruency.....Δ ACB ~Δ ADC → AC /AB = AD/ AC → AC^2 = AB * AD

Similary Δ ACB ~ ΔCDB → AB / BC = BC / DB → BC^2 = AB * DB

So

AC^2 + BC^2 = AB* AD + AB * DB

AC^2 + BC^2 = AB ( AD + DB)

AC^2 + BC^2 = AB (AB)

AC^2 + BC^2 = AB^2

CPhill Aug 31, 2018